Potentiating the Oncolytic Efficacy of Poxviruses - Komar, Monica (Université d'Ottawa / University of Ottawa, 2012)
Several wild-type poxviruses have emerged as potential oncolytic viruses (OVs), including orf virus (OrfV), and vaccinia virus (VV). Oncolytic VVs have been modified to include attenuating mutations that enhance their tumour selective nature, but these mutations also reduce overall viral fitness in cancer cells. Previous studies have shown that a VV (Western Reserve) with its E3L gene replaced with the E3L homologue from, OrfV (designated VV-E3LOrfV), maintained its ability to infect cells in vitro, but was attenuated compared to its parental VV in vivo. Our goal was to determine the safety and oncolytic potential VV-E3LOrfV, compared to wild type VV and other attenuated recombinants. VV-E3LOrfV, was unable to replicate to the same titers and was sensitive to IFN compared to its parental virus and other attenuated VVs in normal human fibroblast cells. The virus was also less pathogenic when administered in vivo. Viral replication, spread and cell killing, as measures of oncolytic potential in vitro, along with in vivo efficacy, were also observed.. The Parapoxvirus, OrfV has been shown to have a unique immune-stimulation profile, inducing a number of pro-inflammatory cytokines, as well as potently recruiting and activating a number of immune cells. Despite this unique profile, OrfV is limited in its ability to replicate and spread in human cancer cells. Various strategies were employed to enhance the oncolytic efficacy of wild-type OrfV. A transient transfection/infection screen was created to determine if any of the VV host-range genes (C7L, K1L, E3L or K3L) would augment OrfV oncolysis. Combination therapy, including the use of microtubule targeting agents, Viral Sensitizer (VSe) compounds and the addition of soluble VV B18R gene product were employed to see if they also enhance OrfV efficacy. Unfortunately, none of the strategies mentioned were able to enhance OrfV.
Keywords: Poxvirus; Vaccinia virus; Orf Virus; Interferon; Host-range genes; Cancer; Oncolytic virus; Combination therapy; E3L